Decreasing partnership (al-mushārakah al-mutanāqisah) for asset and venture financing: realizing Shari‘ah essentials - Sadique, Muhammad Abdurrahman (2011)
Al-mushārakah al-mutanāqiÎah or decreasing equity partnership based modes could be used for financing asset procurement as well as projects in a variety of situations. The shari„ah admissibility of this mode essentially depends on the reality and independent functioning of the various contracts. Diverse capacities the parties undertake through the component contracts should be effectively reflected, especially through fulfilling the duties pertaining to ownership and lease, and accepting the liabilities involved. Gaining legal recognition for the component contracts should be attempted for. In decreasing partnership for ventures, the equity structure should not be based on terms favourable to one party alone. Replacing the legally binding promise to purchase with an understanding to that effect, giving the partners a choice in the matter, could be more conducive towards the equity relationship.